Current and future best practice in imaging, staging, and response assessment for Non-Hodgkin's lymphomas: the Specialist Integrated Haematological Malignancy Imaging Reporting (SIHMIR) paradigm shift. Issue 5 (May 2021) - Zafar, S.; Sharma, R.K.; Cunningham, J.; Mahalingam, P.; Attygalle, A.D.; Khan, N.; Cunningham, D.; El-Sharkawi, D.; Iyengar, S.; Sharma, B.
Abstract : Non-Hodgkin's lymphoma (NHL) encompasses over 40 different haematological malignancies, including low and high-grade neoplasms, such as follicular lymphoma (FL) and diffuse large B-cell lymphoma (DLBCL) respectively. A key clinical issue in the context of NHL is delayed and inaccurate diagnosis, which contributes adversely to patient morbidity and mortality. This article will address relevant imaging aspects, with particular reference to advancements in NHL imaging, including computed tomography (CT), integrated positron-emission tomography (PET)-CT, and magnetic resonance imaging (MRI). We provide multiparametric (anato-functional) imaging display items, including histological correlation. We will also introduce our original concept of "Specialist Integrated Haematological Malignancy Imaging Reporting" (SIHMIR), a paradigm shift in lymphoma radiology.